Forced removals embodied as tuberculosis. (July 2016) - Richardson, Eugene T.; Morrow, Carl D.; Ho, Theodore; Fürst, Nicole; Cohelia, Rebekkah; Tram, Khai Hoan; Farmer, Paul E.; Wood, Robin
Abstract: South Africa has one of the worst tuberculosis burdens in the world. Several ecological forces have contributed to this, including high HIV prevalence; failing TB control strategies; crowded, poorly ventilated indoor environments—including the complex web of political and economic interests which produce them; the development of racial capitalism; and mining and migration. In the following study, we measure CO2 levels in public transport to investigate the role extended commutes from peri-urban settlements to urban sites of work—a direct result of forced removals—potentially play in propagating the TB epidemic in Cape Town, South Africa. Highlights: A critical theory of how social forces become embodied as TB is proposed. By measuring indoor CO2 levels, one can estimate probabilities of TB transmission. Forced removals in South Africa have created extended commutes. Commutes in poorly ventilated transport increase the risk of TB transmission. Environmental interventions and social justice can help end TB.